2015
DOI: 10.2298/jsc150224027z
|View full text |Cite
|
Sign up to set email alerts
|

QTAIM investigation of bis(pyrazol-1-yl)methane derivative and its Zn(II) complexes (ZnLX2, X=Cl, Br or I)

Abstract: Topological analyses of the electron density using the quantum theory of atoms in molecules (QTAIM) have been carried out at the B3PW91/6-31g (d) theoretical level, on bis(pyrazol-1-yl)methanes derivatives 9-(4-(di (1H-pyrazol-1-yl)-methyl)phenyl)-9H-carbazole (L) and its zinc(II) complexes: ZnLCl2 (1), ZnLBr2 (2) and ZnLI2 (3). The topological parameters derived from Bader theory were also analyzed; these are characteristics of Zn-bond critical points and also of ring critical points. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Several quantum chemical parameters have been calculated. 13 The FT-IR, 1 H-NMR and 13 C-NMR Chemical Shifts of the molecule were calculated by the gaugeindependent atomic orbital (GIAO) method and compared with experimental results.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Several quantum chemical parameters have been calculated. 13 The FT-IR, 1 H-NMR and 13 C-NMR Chemical Shifts of the molecule were calculated by the gaugeindependent atomic orbital (GIAO) method and compared with experimental results.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…The optimized bond lengths and bond angles of investigated compounds calculated by B3LYP/LANL2DZ methods with 6-311++G (d,p) basis set were listed in Table S-7 and S-8 following the atom numbering scheme as shown in Fig. 2 (a-d Based on elemental analysis, electronic spectra, ESI-MS, FT-IR, 1 H-NMR, 13 C-NMR and DFT studies, optimized structures of the ligand L is suggested in Fig. 2(a).…”
Section: Bond Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several quantum chemical parameters have been calculated. 21 The 1 H-NMR and 13 C-NMR Chemical Shifts of the molecule were calculated by the gauge-independent atomic orbital (GIAO) method and compared with experimental results. DFT was employed to study the energy profiles of the full catalytic cycle of complex 1 for the Heck-Mizoroki reaction.…”
Section: Dft Calculationmentioning
confidence: 99%
“…The di(1H-pyrazol-1-yl)methane (2) has been studied theoretically [PBE0/6-31+G(d,p)] and its IR spectrum measured and compared with the calculated one [267]. A QTAIM investigation of compound 293 was carried out based on its X-ray structure [268].…”
Section: Computational Studiesmentioning
confidence: 99%